THE ROLE OF ETHICAL LEADERSHIP AND WHISTLEBLOWING INTENTIONS: MEDIATING APPARATUS OF MORAL IDENTITY (American International Journal of Humanities, Arts and Social Sciences, 2021)
Separation of strategic approaches and morals prompted various business outrages and untrustworthy practices in working environments. This encouraged researchers and practice holders to examine significance of ethical quality at work environment. In particular, the job that moral chiefs play in advancing positive representative practices is urgent. This examination article has featured the part of moral innovators in molding whistleblowing goals of their subordinates. Alongside, this exploration article has likewise researched the part of good character. An aggregate of four speculations, analyzing the immediate impact of moral initiative on moral personality and whistleblowing expectations and meditational job of good character were proposed. This exploration article embraced a period slacked research article plan and gathered data from representative friend dyads at three focuses on schedule. Number of respondents was 214; Cross-sectional technique was used for data collection. Respondents were selected from different services organizations from Multan. Data was analysed on SPSS and AMOS. Results were obtained by applying reliability test, ANOVA, Correlation test, and regression test by using PROCESS Macro. Results gained verified that the role of ethical leaders in shaping moral identity of employees as well as their whistleblowing intentions. The findings suggest that employees working under ethical leaders are inclined to stand up against malevolent and unethical practices taking place at their workplace. Thus, organizations must hire leaders with higher ethical inclinations and also train the existing leaders about importance of ethics. Moreover, this research article has highlighted multiple avenues for future research.